Lesson Learned from the Successfulness of Nurses’ Leaders in the Management of Comprehensive Covid-19 Vaccination Service: A Case Study in Vaccination Center, Songkhla - Atthawong, Phensiri; Songwathana, Praneed (Princess of Naradhiwas University Journal, 2023)
Corona virus 2019 (COVID-19) has rapidly and widely caused impacts to society. Seeking methods to reduce the severity and control the pandemic of COVID-19 is essential and one of the most significant methods which globally implemented including Thailand was vaccination. However, providing COVID-19 vaccine for all targeted population in a short period of time is an extremely challenging task for health care providers and it required a systematic management. This article is presented regarding experiences of nurses’ leaders in managing and providing Covid-19 vaccination services to all people equally within the limited time by designing working process and mobilizing resources in order to reduce work load of workers in the vaccination center in achieving the target. As a result, a Covid-19 vaccination service management has been applied in this research for people in surrounding areas that are under the responsibility of Songkhla hospital which located in and categorized as a red zone (or high risk of pandemic areas) to refer to as a case study. The outcomes found from this lesson learned were divided into 3 stages: 1) Preparing and testing the readiness of an operating service system such as searching for the target group to be vaccinated, setting a plan and forming a team immediately, meeting and testing for a service readiness 2) Implementing a comprehensive vaccination service, and 3) Evaluating the service. The finding was found that the management has achieved the key result indicator in terms of the target citizen including 608 group (the group of 60 years old or older, seven chronic diseases, and pregnancy) who had been vaccinated which were higher than 70 percent and the client were satisfied with the service received from the vaccination center without any complaints.